‘I do hope more people can benefit from it.’: The qualitative experience of individuals living with osteoarthritis who participated in the GLA:D™ program in Alberta, Canada - Kania-Richmond, Ania; Beaupre, Lauren A.; Jessiman-Perreault, Geneviève; Tribo, Danika; Martyn, Jason; Hart, David A.; Robert, Jill; Slomp, Mel; Jones, C. Allyson (PLOS ONE, 2024)
Introduction The Good Life with osteoArthritis: Denmark (GLA:DTM) is an evidence-based program designed for individuals with symptomatic hip and knee osteoarthritis (OA). This program has reported improvement in pain, quality of life and self-efficacy, as well as delays in joint replacement surgery for adults with moderate to severe hip or knee OA. Evaluations of GLA:DTM implementation in several countries have focused on effectiveness, training, and feasibility of the program primarily from the provider perspective. Our objective was to examine how the GLA:DTM program was perceived and experienced by individuals with hip and knee OA to inform on-going program refinement and implementation. Methods Thirty semi-structured telephone interviews were conducted with participants who completed the GLA:DTM program in Alberta. An interpretive description approach was used to frame the study and thematic analysis was used to code the data and identify emergent themes and sub-themes associated with participants’ experience and perception of the GLA:DTM program. Results Most participants had a positive experience of the GLA:DTM program and particularly enjoyed the group format, although some participants felt the group format prevented one-on-one support from providers. Three emergent themes related to acceptability were identified: accessible, adaptable, and supportive. Participants found the program to be accessible in terms of location, cost, and scheduling. They also felt the program was adaptable and allowed for individual attention and translatability into other settings. Finally, most participants found the group format to be motivating and fostered connections between participants. Conclusion The GLA:DTM program was perceived as acceptable by most participants, yet the group format may not be useful for all individuals living with OA. Recommended improvements included adapting screening to identify those suited for the group format, providing program access earlier in the disease progression trajectory, modifying educational content based on participants’ knowledge of OA and finally, providing refresher sessions after program completion.